Perception of Compliance and Awareness of Paying Taxes After the Tax Fraud Phenomenon - Cahyani, Amalia Regita; Mustofa, Rochman Hadi (International Journal of Science and Society, 2024)
The phenomenon of misappropriation of funds by tax officials is considered to have an influence on public compliance and awareness in paying taxes. This encourages researchers to conduct research on perceptions of compliance and awareness of paying taxes after the tax fraud phenomenon. The aim of this research is to describe in detail the views of the general public regarding the influence of the issue of tax fraud on tax compliance by taxpayers. The research method used is qualitative using a phenomenological approach with data collection techniques through interviews and observations of research instruments composed of ASN, MSMEs and students. This research was conducted from April to June 2023. The data collected was then analyzed in depth to determine the research results. The research results show that the abuse of authority of tax officers in utilizing tax funds can influence the public's perception of being obedient and aware in paying taxes, because one of the factors that plays a role in increasing taxpayer compliance and awareness is tax officers. For this reason, the government needs to disseminate information about taxes to the public and take firm action against tax officials who commit irregularities so that public trust improves again.